(untitled) (Research, Society and Development, 2021)
Since the beginning of the pandemic, several drugs have been studied as alternatives to treat COVID-19 infection. These include chloroquine, ivermectin, hydroxychloroquine and nitazoxanide. The present study sought to identify the knowledge and behavior about the use of drugs without scientific evidence in part of the population of the state of Pará, during the COVID-19 pandemic. The research adopted a descriptive and prospective approach, involving a questionnaire in an electronic form, to collect data from residents of the state. The results showed that the frequency of individuals who believed in early treatment and/or use of medication as prophylaxis was higher in residents of cities in the interior of the state and in older age groups, despite the contrary scientific findings. In the population studied, 9.9% of residents in other cities did not believe that vaccines were safe and effective, and 7.0% reported that only a few would be. The ideological orientation of a part of the population and anti-vaccination movements can partly explain the results presented. The inappropriate use of drugs for the early treatment and/or prophylactic use of COVID-19 is still a reality in the state of Pará, and public policies must be implemented to curb such use and increase actions that seek to raise awareness about the importance of vaccination and maintenance of scientifically proven prevention measures.